Atomic‐Level and Modulated Interfaces of Photocatalyst Heterostructure Constructed by External Defect‐Induced Strategy: A Critical Review. Issue 1 (8th December 2020) - Zhang, Shuqu; Si, Yanmei; Li, Bing; Yang, Lixia; Dai, Weili; Luo, Shenglian
Abstract: Despite the existence of numerous photocatalyst heterostructures, their separation efficiency and charge flow precision remain low due to the poor study on interfacial properties. The photocatalysts with confined defects can effectively control the photogenerated carrier migration, but the metastability of such defects considerably decreases the photocatalyst stability. Meanwhile, the introduction of defective region can increase the coordinative unsaturation and delocalize local electrons to promote their interactions with the molecules/ions in that region. The selective growth of modulated heterogeneous interface by defect‐induced strategy may not only increase the stability of defective structures, but also enhance the migration of interfacial charges. Using this method, photocatalytic heterostructures with low contact resistances and intimate interfaces are constructed to achieve the optimal charge migration in terms of efficiency and accuracy. In this work, the point, linear, and planar heterogeneous interfaces and related defect engineering techniques are discussed. Particularly, it is focused on the external, defect‐induced interfacial heterogeneities with various spatial and dimensional configurations, which exhibit modulated and controllable interfacial properties. Furthermore, the main aspects of fabricating photocatalyst heterostructures by the defect‐induced strategy, including the i) controllable generation of defects, ii) advanced characterization methods, and iii) elaborate construction of the minimal interface, are described. Abstract : The heterostructures constructed in the defective areas containing new active sites not only solve the metastability problem of defective structures, but also exhibit unique architectures and spatially modulated properties that preserve their high efficiencies. Eventually, the atomic‐level and modulated interfaces can be customized masterly by regulating defect property, transforming a common interface to a defective interface.